Photovoltaic performances of Cu2-xTe sensitizer based on undoped and indium3+-doped TiO2 photoelectrodes and assembled counter electrodes - Srathongluan P. (2017)
© 2015 Elsevier Inc. Novel binary Cu 2-x Te nanoparticles based on undoped and indium-doped TiO 2 photoelectrodes were synthesized using a successive ionic layer adsorption and reaction (SILAR) technique as a sensitizer for liquid-junction solar cells. A larger diameter of TiO 2 promoted a narrower energy band gap after indium doping, attributing to yield a broader absorption range of nanoparticle sensitizer due to the increasing amount of Cu 2-x Te NPs on TiO 2 surface. The atomic percentages showed the stoichiometric formation of Cu 2 Te incorporated in a Cu 2-x Te structure. The best photovoltaic performance with the lower SILAR cycle, i.e., n=13 was performed after indium doping in both of carbon and Cu 2 S CEs and revealed that the efficiency of 0.73% under the radiant 100 mW/cm 2 (AM 1.5G). The electrochemical impedance spectroscopy (EIS) was used to investigate the electrical properties via effect of material doping and counter electrodes with a lower charge-transfer resistance (R ct ) and it was also found that the electron lifetime was improved after the sample doped with indium and assembled with carbon CE.